55 High-sensitivity cardiac troponin T and risk of hypertension. (7th October 2015) - McEvoy, JW; Chen, Y; Nambi, V; Ballantyne, CM; Sharrett, RA; Appel, LJ; Post, WSS; Blumenthal, RS; Matsushita, K; Selvin, E
Abstract : Background: Hypertension is often preceded by cardiac structural abnormalities. Thus, we assessed whether high-sensitivity cardiac troponin-T (hs-cTNT), a marker of chronic subclinical myocardial damage, can identify persons at risk for hypertension or left ventricular hypertrophy (LVH). Methods and results: We studied 6, 516 ARIC Study participants, free of prevalent hypertension and cardiovascular disease at baseline (1990–1992). We examined the association of baseline hs-cTNT categories with incident diagnosed hypertension (defined by self-report of a diagnosis or medication use during a maximum of 19.9 years of follow-up) and with incident visit-based hypertension (defined by self-report, medication use, or measured BP >140/90 mmHg over 6 years). Relative to hs-cTNT <5 ng/L, adjusted hazard ratios for incident diagnosed hypertension were 1.16 (95% CI 1.08, 1.25) for persons with hs-cTNT 5–8 ng/L, 1.29 (1.14, 1.47) for hs-cTNT 9–13 ng/L, and 1.31 (1.07, 1.61) for hs-cTNT ≥14 ng/L (p-trend <0.001). Associations were stronger for incident visit-based hypertension. These associations were driven by higher relative hazard in normotensive persons (relative to those with prehypertension, p-interaction = 0.001). Baseline hs-cTNT was also strongly associated with incident LVH by electrocardiography over 6 years (e.g. adjusted HR 5.19 [1.49–18.08] for hs-cTNT ≥14 ng/L vs <5 ng/L). Findings were not appreciably changed after accounting for competing deaths or adjustment for baseline BP levels or NT-proBNP. Conclusion: In an ambulatory population with no history of cardiovascular disease, hs-cTNT was associated with incident hypertension and risk of LVH. Further research is needed to determine whether hs-cTNT can identify persons who may benefit from ambulatory BP monitoring or hypertension prevention lifestyle strategies.